Capital flows and crises - Eichengreen, Barry J. (MIT Press, 2003)
The implications of capital mobility for growth and stability are some of the most contentious and least understood contemporary issues in economics. In this book, Barry Eichengreen discusses historical, theoretical, empirical, and policy aspects of the effects, both positive and negative, of capital flows. He focuses on the connections between capital flows and crises as well as on those between capital flows and growth. Eichengreen argues that international financial liberalization, like other forms of economic liberalization, can positively affect the efficiency of resource allocation and the rate of economic growth. But analyses of both recent and historical experience also show an undeniable association between capital mobility and crises, especially when domestic institutions are weak and the harmonization of capital account liberalization and other policy reforms is inadequate. In his conclusion, Eichengreen makes suggestions for policy design to maximize the benefits of international financial liberalization while minimizing the risks of financial instability.